Shallow whole genome sequencing of adenoid cystic carcinomas of the salivary glands identifies specific chromosomal aberrations related to tumor progression. (April 2020) - Cordesmeyer, R.; Laskawi, R.; Schliephake, H.; Kauffmann, P.; Beck, J.; Bornemann-Kolatzki, K.; Schütz, E.; Ströbel, P.; Kueffer, S.; Fichtner, A.; Bremmer, F.
Highlights: Chromosome 6, 12 and 4 showed an increased frequency of chromosomal alterations. Molecular evolution from primary tumors to local recurrences and distant metastases. These regions should be in the focus of the search for therapeutic targets of ACC. Abstract: Background and Purpose: Adenoid cystic carcinomas (ACC) are characterized by high rate of local recurrence and late distant metastasis. Chromosomal changes in the evolution from primary tumors to metastatic disease of ACC have not been appointed. Here we investigated the chromosomal alterations of 53 primary tumors from ACC patients with different progressive states by shallow whole genome sequencing to identify potential new markers for metastatic spread. Methods: Illumina paired-end libraries were generated using DNA from the primary tumor of 53 ACC patients. Fragmented DNA was end-repaired, A-tailed and multiplex sequencing adapters were ligated. Sequence data were mapped to HG19 and a copy-number analysis was conducted using the QDNAseq R package (version 1.10.0). Outliers were removed and data was smoothed by applying the circular binary segmentation algorithm implemented in the R package copynumber version 1.22.0. A modified chromosomal instability (CNI) score was used to analyze deletions and amplifications. Results: Cluster analysis of the whole genome sequencing revealed that the frequency of chromosomal aberrations were increased in ACC with local recurrence and distant metastases in comparison to ACC patients with no metastatic spread. Specifically, chromosome 6 and 12 and exclusively the entire chromosome 4 showed an increased frequency of chromosomal alterations with tumor progression. Conclusion: Our data show a molecular evolution from primary tumors to local recurrences and distant metastases and pinpoint the critical chromosomal regions involved in this process. These regions should be in the focus of the search for therapeutic targets of progressive ACC.